1997
DOI: 10.1128/cdli.4.5.583-586.1997
|View full text |Cite
|
Sign up to set email alerts
|

Soluble interleukin-2 receptor is a thyroid hormone-dependent early-response marker in the treatment of thyrotoxicosis

Abstract: Thyrotoxic patients exhibit increased levels of immune activation molecules (soluble interleukin-2 receptor [sIL-2R], intercellular adhesion molecule-1 [ICAM-1], and endothelial-leukocyte adhesion molecule-1 [ELAM-1]) in serum, although the clinical significance of these measurements remains unclear. In a randomized 4-week study, we have recently shown that in the treatment of hyperthyroidism, the combination of cholestyramine and methimazole (MMI) resulted in faster lowering of serum thyroid-hormone levels th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…In agreement with this, a strong positive correlation of sIL-2R with FT4 and negative correlation with TSH were found. The results are in agreement with the literature and show that serum concentrations of sIL-2R in GD patients are related to the thyroid function rather than to activation of immunity [14].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with this, a strong positive correlation of sIL-2R with FT4 and negative correlation with TSH were found. The results are in agreement with the literature and show that serum concentrations of sIL-2R in GD patients are related to the thyroid function rather than to activation of immunity [14].…”
Section: Discussionsupporting
confidence: 92%
“…Wakelkamp and colleagues have also observed elevated serum levels of both sTNF-receptors in patients with Graves' disease exhibiting euthyroid states [27]. For comparison, sIL-2R serum levels may be enhanced in Graves' thyroid disease due to a hypermetabolic stage leading to increased thyroid function as well as by thyroid autoimmune processes [23], as recent data suggested a role for thyroid hormone in the activation of immune cells and the release of cytokines and sIL-2R in the serum [24]. In contrast to the presented data on sIL-2R, we found sTNF-RI to be statistically significantly correlated to TRAb, indicating a closer relation with the autoimmune mechanisms of Graves' disease compared to sIL-2R in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The patients of this study were not immunocompromised and made an uneventful recovery, so in this setting, we can also speculate (given the small overall variations), a relation between thyroid hor mones and sIL-2R in the low-T3 syndrome. Since the measurement of sIL-2R has already been proposed as an indicator of disease activity in Graves' disease (11) and an early response marker in thyrotoxicosis' treatment (5), further relevant studies can be envisaged, in order to assess the behavior and clinical utility of sIL-2R levels versus thyroid function parameters in non-thyroidal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Normal peripheral blood mononuclear cells and certain lines of T-and B-cell origin release, after its membrane expression, a soluble form of interleukin-2 receptor (sIL-2R); this appears to be a consequence of cellular activation of various cell types that may play a role in the regulation of the immune response (1,2) . Patients with autoimmune diseases, haematologic malignant diseases or overt thyroid disease often show high sIL-2R serum levels (3,4,5), however the course of sIL-2R levels in non-thyroidal disease affecting thyroid function has not been adequately explored. Recent studies have shown that patients with tuberculosis (TB) present with low to normal free and total triiodothyronine levels, which rapidly elevate after anti-TB treatment (6,7,8).…”
Section: Introductionmentioning
confidence: 99%